Sensory analysis and acceptability of honey from different blossoms from three municipalities in the Northeast of Pará (Research, Society and Development, 2021)
Honey is by man as a food and for its therapeutic properties since prehistory, besides being a great source of several nutrients, in this sense it is important to know the relationship that consumers have with this food. Therefore, the objective of this work was to evaluate the sensory profile and the acceptability of honey from three different floral origins. The experiment was carried out in October 2019, at the Food Technology Laboratory of the Federal Rural University of the Amazon, on the Paragominas campus, Pará. Three samples of honeys of different floral origins were used, one from Terra Alta, Pará, another sample from the city of Primavera, Pará, and finally, the last sample was from the city of Santa Maria, Pará. The evaluators read and signed an informed consent form and subsequently completed a structured questionnaire. The acceptability test was applied, using the nine-point hedonic scale. The intention to purchase honey samples was assessed using a five-point structured scale. The data were organized in Microsoft Excel spreadsheets. To verify which honey sample was most accepted by the evaluators, the Kruskal Wallis non-parametric test was performed, with the aid of the SPSS software. In general, the sample that obtained the greatest acceptance was sample B, followed by sample C and lastly sample A.